Strengthening Community Seed Banks for Gender inclusive development in India - Rengalakshmi, Raj; Puskur, Ranjitha; Pratheepa, C. M.; Gopinath, R.; Tenneti, Suchaita; Bomuhangi, Allan (CGIAR Initiative on Seed Equal, 2024)
The formal seed system in India mainly includes seeds of notified varieties and important crops, predominantly produced for markets. However, it faces challenges in meeting the diverse crop and varietal needs of small and women farmers in marginal agroecosystems. Most importantly, formal seed systems have less space for women to access preferred varieties, knowledge, market potential, and institutional linkages due to existing gender norms. Women have also not been actively participating and making decisions on the use of improved varieties in food systems. They largely depend on informal seed systems to access seeds. However, with changing agrarian relations and structures, informal seed systems face challenges in ensuring equitable access to traditional and community-preferred landraces or varieties from informal social networks, connections, and exchanges. At the field level, these changes adversely impact women and marginal farmers’ access to preferred crops and varieties/ landraces, gender relations, food and nutrition security, dietary diversity, food systems resilience, and livelihoods. Against this backdrop, the Community Seed Banks (CSB) model has evolved as an important component in the informal seed system to ensure access to traditional varieties of different crops, specifically neglected and under-utilized crop species.